Leveraging AI for Strategic Decision-Making in Indonesia's National Defense Management - Yusman, Faisal; Muhammad Taufik, Robby; Yanda Dwira Firman (PERSPEKTIF, 2025)
Strategic decision-making processes are critical in navigating the complex and ever-changing domain of national defense. In the Indonesian context, the use of Artificial Intelligence can offer a transformative approach to enhance this critical decision-making framework. This research paper examines the potential of an AI-based strategy to support and strengthen Indonesia’s national defense management. The study explores the current state of AI implementation in the industrial sector, the role of performance management in optimizing AI-based systems, and the contribution of AI in achieving sustainable development goals. The findings suggest that a comprehensive national strategy for AI can open up significant opportunities for Indonesia to strengthen its national defense capabilities, drive innovation, and secure its position in the global geopolitical landscape.